Fascin-1 expression as stratification marker in borderline epithelial tumours of the ovary. Issue 2 (11th September 2015) - El-Balat, Ahmed; Arsenic, Ruza; Sänger, Nicole; Karn, Thomas; Becker, Sven; Holtrich, Uwe; Engels, Knut
Abstract : Aims: To evaluate the actin-bundling protein fascin-1 (FSCN1) as marker for borderline ovarian tumours (BOTs). Methods: We analysed a retrospective cohort of 140 BOTs with validated diagnosis by an independent pathologist. Immunohistochemical detection of FSCN1 was quantified as combined immunoreactive score (CIS) blinded to clinical patient data. Analyses were first performed for FSCN1 positive versus negative, and then verified using three categories derived from the observed distribution (negative, weak, strong; CIS 0, 1–2, 3–9). Results: We detected FSCN1 positivity in 51.4%, and strong expression (CIS 3–9) in 14.3% of the samples. FSCN1 positivity was associated with serous subtype (p<0.001) and micropapillary pattern (p<0.001). Correlation with micropapillary pattern remained significant within the serous BOT (SBOT) subgroup (p=0.022). Strong FSCN1 expression (CIS 3–9) was associated both with the presence of implants (p=0.022), and a higher International Federation of Gynecology and Obstetrics (FIGO) stage (p=0.020). Conclusions: Our analysis links FSCN1 with SBOT with micropapillary pattern. Strong expression is associated with higher FIGO stage and the presence of implants, both related to elevated risk of recurrence. Hence, FSCN1 is an interesting marker worth further analyses of its prognostic value in BOTs.